Marketing planning & strategy : a practical introduction - Dawes, John (Thousand Oaks : SAGE Publications Ltd., 2021)
'This new book guides you concisely through the marketing planning process from start to finish, drawing on examples from large brands like Ikea and Krispy Kreme to digital start-ups like Starling Bank'--
Keywords: Marketing; Marketing -- Management